Surface roughness and wettability investigation of varied plasma parameter effect on PVD deposited aluminium - Moganraj, Palianysamy
Surface metrology has been a focused and thoroughly investigated research niche since the advent of device fabrication. The current technology shift into MEMS and nano has again made surface metrology a focused area. Layer adhesion and bonding have surface metrology importance here. In this work, surface of aluminium bond pad is characterized using water droplet test and Atomic Force Microscopy(AFM) analysis. Full Factorial Experiment Design was used to carry out this experimental study. Aluminium was deposited using Physical Vapor Deposition(PVD) technique. Water droplet test was done using a prepared test chamber. The surface was treated using plasma parameter, whereby the plasma parameter and roughness were correlated. Plasma parameter was manipulated in two different experiment approaches. First experiment was using a combination of oxygen gas flow, argon gas flow, ICP power and Bias power. Second experiment consist of Carbon Tetrafluoride(CF4) gas flow, Argon gas flow, ICP power and BIAS power. Results of surface characterization were analyzed using statistical analysis comprising main effect analysis and interaction between factor analyses. This provides the effect of each factor and combination of factors which affects the outcome of the experiment. This correlation of plasma parameter to surface roughness and water droplet test will enable us to understand aluminium surface manipulation for bonding and other adhesion purposes. Final results shows that the experiment comprising of Carbon Tetrafluoride(CF4)gas flow, Argon gas flow, ICP power and BIAS power produces surface with a higher hydrophilicity characteristics proven by the measured contact angle which averages at 56°. The surface roughness value range from 2.46nm to 19.53nm Whereas, experiment comprising oxygen gas flow, argon gas flow, ICP power and BIAS power produces lower hydrophilic character surfaces which has a higher average contact angle which is 70°.This contact angles are produced by surface roughness ranging from 4.09nm to 20.09nm.